The External Stimuli Which Drives Impulsive Buying Behavior: Case Study On Users Of Indonesia’s Large E-Commerce Platforms - Adi Waskito; Anisha Marjani Putri Firaldi; Arviga Bigwanto; Citra Jayanti Yuwono (Institut Manajemen Wiyata Indonesia & Asosiasi Peneliti Manajemen Indonesia, 2023)
In the past five years, people are becoming more accustomed to online purchases especially due to health measures taken as a response to the 2020 pandemic. Indonesia led all other ASEAN countries in terms of online purchases. In this study, we examined the relationship between external stimuli and impulse buying behaviour on e-commerce platforms. We conducted an online survey and found that quality of information, and e-wallet use have a positive influence on driving impulsive buying behaviour. For e-commerce business owners, these findings are helpful to determine areas to focus on when improving e-commerce. The theories underlying this research are Technology Acceptance Model Modified I introduced by Venkatesh and Davis (1996) and the concept of Impulse Buying Behavior by Gulfraz et al (2022). The research design was mainly developed from previous research by Kimigiari and Malafe (2021). In this research which involved 419 respondents, sampled with purposive sampling method and using online questionnaire as instrument, it can be concluded that in Indonesia case, the quality of information and e-wallet use impacts impulsive buying behavior tendencies.